163k views
5 votes
Trent writes p^2 + 30 = (p + 30)(p + 0)

Do you agree with Trent? Explain why

User Phflack
by
5.1k points

1 Answer

5 votes

Answer:

Statement expressed by Trent is RIGHT.


(p^2 + 30) = (p+30)(p +0)

Explanation:

Here, the given expression is:

( to show) :
(p^2 + 30) = (p+30)(p +0)

Now, as we know by DISTRIBUTIVE PROPERTY:

A (B + C) = AB + AC

Consider the RHS of the expression:

(p +30)(p+0) = (p +30)(p) ............ ( a + 0 = a for all a)

Simplifying (p +30)(p) by distributive property, we get:


(p +30)(p)   = p(p) + 30(p) \\= p^2 + 30p\\\implies (p+30)(p+0)  =  p^2 + 30p

⇒ Left side = Right side

Hence, statement expressed by Trent is RIGHT.

User Fer Toasted
by
4.4k points